Application of global thresholding in bread porosity evaluation - Bosakova-Ardenska, Atanaska (International Journal of Intelligent Systems and Applications in Engineering, 2015)
The white bread is one of most popular food in Bulgaria. Its quality is defined by standards and control is also standardized. The white bread has four groups of quality parameters - organoleptic, physicochemical, chemical contaminants and microbiological. This paper presents one research over white bread porosity which is one of physicochemical parameters. By standard evaluation of bread porosity is time expensive procedure. Current research proposes one fast computer based approach for white bread porosity evaluation. In experiments are used three brands white breads. The images of breads are binarized with four known algorithms and coefficient of diversity (ratio of white pixels and all image pixels) for resulting binary images is calculated. This coefficient corresponds with bread porosity. Experimental results show that one of these algorithms â Vector Median Thresholding, is appropriate for bread porosity evaluation.